Bringing Ben home : a murder, a conviction, and the fight to redeem American justice - Bradley Hagerty, Barbara (Riverhead Books, 2024)
"In 1989, Ben Spencer was convicted of murdering businessman Jeffrey Young-a crime he didn't commit. Spencer to spent more than half his life in prison until independent investigators, the foreman of the jury that convicted him, and a new district attorney convinced a judge that Spencer had nothing to do with the killing. He was released from prison in 2022. Journalist Barbara Bradley Hagerty spent years immersed in Spencer's case. She combed police files and court records, interviewed dozens of witnesses, and had extensive conversations with Spencer. In Bringing Ben Home, she weaves together two narratives: how an innocent Black man got caught up in and couldn't escape a legal system that refused to admit its mistakes; and what Texas and other states are doing to address wrongful convictions to make the legal process more equitable for everyone"--